2021
DOI: 10.1021/acs.cgd.0c01138
|View full text |Cite
|
Sign up to set email alerts
|

Taking the Third Route for Construction of POMOFs: The First Use of Carboxylate-Functionalized MnIII Anderson–Evans POM-Hybrid Linkers and Lanthanide Nodes

Abstract: The purpose of the present contribution is to illustrate how to design and grow crystals of POMOFs based on POM-hybrid linkers with lanthanide ions as nodes. Thus, the MnIII-centered Anderson–Evans polyoxometalate (Mn-A-E-POM) was functionalized with 4-(((1,3-dihydroxy-2-(hydroxymethyl)­propan-2-yl)­amino)­methyl)­benzoic acid (H4L) to afford the hybrid inorganic–organic POM [N­(n-C4H9)4]4[(MnMo6O18)­(HL)­(L)] (1), which in turn reacts with lanthanide salts and yields two three-dimensional frameworks with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Anderson-type POM-MOFs have also attracted increasing interest. [112][113][114][115][116][117][118][119] In 2016, Wang et al 19a). 116 Furthermore, this material can serve as an electrocatalyst and used for electrocatalytic reduction of NO2 -, Cr(VI) and BrO3as well as the electrocatalytic oxidation of ascorbic acid.…”
Section: Anderson-type Pom-mofsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anderson-type POM-MOFs have also attracted increasing interest. [112][113][114][115][116][117][118][119] In 2016, Wang et al 19a). 116 Furthermore, this material can serve as an electrocatalyst and used for electrocatalytic reduction of NO2 -, Cr(VI) and BrO3as well as the electrocatalytic oxidation of ascorbic acid.…”
Section: Anderson-type Pom-mofsmentioning
confidence: 99%
“…18g). Apart from the most commonly used copper ions, Powell et al launched the study on the reactivity of RE cations with carboxylate-functionalized Anderson-type precursor [N(n-C4H9)4]4[(MnMo6O18)(HL)(L)] (H4L = 4-(((1,3-dihydroxy-2-(hydroxymethyl)-propan-2-yl)amino)methyl)benzoic acid) and discovered two families of 3-D POM-MOFs [RE(DMF)6RE(DMF)5RE3(DMF)10[(MnMo6O18)(L)2]3•xDMF (RE = La 3+ -Nd 3+ ) and [RE(DMF)4(H2O)]2[RE3(DMF)6][(MnMo6O18)(L)2]3•xDMF (RE = Y 3+ , Sm 3+ -Lu 3+) 119. The difference of these two kinds of Anderson-type POM-MOFs mainly stems from the lanthanide contraction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Covalently modified POMs can further form hybrid functional materials containing frameworks [31][32][33][34] , polymers and other nanostructures [35][36][37][38][39] by coordination assembling with metal ions or metal clusters. Metal-organic frameworks (MOFs) were a kind of porous crystalline materials, which were formed by self-assembly of metal ions/clusters with organic ligands via coordination bonds.…”
Section: Coordination Assembly Of Covalently Modified Pomsmentioning
confidence: 99%
“…Forgan et al reported the coordination assembly of pyridine-appended Mn-Anderson clusters with Zn 2+ and Cu 2+ into two-and three-dimensional network solids with connectivity and topology [31] . The covalently modified POMs can also be coordinated with Cu + , Ag + , Fe 2+ , lanthanide ions and metal clusters [32][33][34]40] . Discrete supramolecular coordination complexes were prone to form multilevel self-assembled structures through non-covalent interactions.…”
Section: Coordination Assembly Of Covalently Modified Pomsmentioning
confidence: 99%